The Effect of Dentin Desensitizer and Nd: YAG Laser Pre-Treatment on Bond Strength of Ceramic Restoration Cemented with Two Self Adhesive Cements - Küçükekenci Ahmet Serkan; Küçükekenci Funda Fundaoglu (The Journal of Dentists, 2018)
Objectives: This in-vitro study evaluated the effects of desensitizing treatments on the shear bond strength (SBS) of ceramic restoration cemented with two different self-adhesive resin cements (SARC). Materials and Methods: Sixty human molars’ occlusal surfaces were ground to expose dentin; and were randomly grouped as (n=10); Group CU: no surface treatment (control) and applied Rely X U200 SARC, Group CP: no surface treatment (control) and applied Panavia SA SARC, Group TU: treated with Teethmate and applied Rely X U200 SARC, Group TP: treated with Teethmate and applied Panavia SA SARC, Group LU: treated with Nd:YAG laser and applied Rely X U200 SARC, Group LP: treated with Nd:YAG laser and applied Panavia SA SARC. Then, lithium-disilicate ceramics (IPS e.max CAD Ivoclar Vivadent: n= 60; 5 mm in diameter; 2 mm in height) were cemented. SBS test was performed and the data were statically analyzed (?=0.05). Failure modes were determined with stereomicroscope. Results: Nd: YAG laser treatment groups showed significantly different SBS values than the control groups (p<0.05). However, there were no significant differences between TMD treatment groups and other groups (p>0.05). Multiple comparisons showed that no statically significant difference found between the SBS values of all groups (p>0.05). Group CP showed the lowest SBS value (14.97 MPa) and Group TU showed the highest SBS value (20.82 MPa) among all experimental groups. The overall failure types for specimens were “mixed” and“ adhesive”. Conclusions: Teethmate desensitizer and Nd:YAG laser pre-treatment increase the SBS of ceramic restoration cemented with two self adhesive cements.